Electric motors AC motor controllers 1 - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the basic functions and operation of AC motor controllers. After completing this unit, trainees should be able to explain how an AC motor controller operates and describe the operation of master switches and pilot devices that can be used with AC motor controllers. They should also be able to explain how an AC motor can provide overload protection and low voltage protection, and to describe the operation of special types of AC motor controllers.
Keywords: Electric motors; Electric controllers